The Central Nervous System Effects and Mimicry of Common Variable Immunodeficiency (CVID): A Case Report with Literature Review - Sohail Farshad; Fernando Figueroa Rodriguez; Alexandra Halalau; Joseph Skender; Cory Rasmussen; Martin Pevzner (Case Reports in Rheumatology)
There is a scarceness of information on the central nervous system effects of common variable immunodeficiency (CVID). A 30-year-old woman with a history of recurrent upper respiratory infections, vitiligo, and immune thrombocytopenic purpura presented with right-sided numbness. Magnetic resonance imaging (MRI) of the thoracic spine revealed a signal hyperintensity. MRI of the brain demonstrated FLAIR hyperintensity in the right middle frontal gyrus. Cerebral spinal fluid was unremarkable. Serum immunoglobulins revealed hypogammaglobulinemia. Endobronchial and subsequent mediastinum biopsies were all negative for sarcoidosis and malignancy. No infectious etiology was found. She was treated with glucocorticoids and intravenous immunoglobulin (IVIG) replacement therapy for CVID-associated myelitis. Follow-up MRI showed improvement; however, her numbness persisted despite these treatments, which led to an outside physician adding methotrexate for their suspicion of sarcoidosis. Her symptoms remained stable for two years, but when the methotrexate dose was weaned, her numbness worsened. Upon review, the treatment team refuted the diagnosis of sarcoidosis but continued treatment with prednisone, IVIG, and methotrexate for CVID-associated myelitis, from which her symptoms have stabilized. Here, we discuss CVID-associated neurological complications, its similarities to sarcoidosis, and a literature review with treatment regimens and outcomes.